DUANE SYNDROME:: OPTOMETRIC MANAGEMENT - Paulino, Elias; Trentin Sonoda, Rodrigo; Carolina Grellet, Ana (Health and Society, 2023)
Duane Syndrome is a rare disorder, also known as Stilling-Turk-Duane Syndrome, which can produce a form of congenital strabismus, most often sporadic, presented by autosomal dominant inheritance, leading to difficulties in ocular motility due to alterations or failures in the innervation of the lateral rectus muscle innervated by the Vl cranial nerve. On this occasion, limitation or absence of abduction, retraction of the eyeball and palpebral narrowing are observed. Binocular vision is compromised, and there is no fusion of images, and the presence of torticollis is common. The prevalence is higher in females and commonly in the left eye. The evaluation takes place through Electromyography. The objective is through a literature review indexed on the platforms Bireme, NiH, Google Scholar and Scielo to demonstrate to primary visual health professionals, especially optometrists, the identification and conduct for these disorders.